Infective endocarditis and COVID -19 coinfection: An updated review - George, Anu; Alampoondi Venkataramanan, Sai Vikram; John, Kevin John; Mishra, Ajay Kumar (Acta Biomedica Atenei Parmensis, 2022)
With the rising number of COVID-19 patients, there have been reports of patients presenting with concomitant infective endocarditis.  In this retrospective review, we included all articles from Medline with COVID-19 and infective endocarditis coinfection.  Ten articles were identified from eight different countries over the world over the past 11 months.  All patients reported with the above coinfections were male with a mean age of 53 years.  Clinical features of COVID-19 and the presence of ground-glass opacity in CT thorax were predominant among patients with positive RT-PCR for COVID-19.  New-onset embolic infarct, pulmonary edema was a contributor to the diagnosis of endocarditis in most patients.  Involvement of the aortic valve was most common.  Delayed diagnosis and cardiac surgery were contributors to increased morbidity.